Simultaneously enhanced strength and ductility of Mg-Zn-Zr-Ca alloy with fully recrystallized ultrafine grained structures. (1st April 2017) - Zheng, Ruixiao; Bhattacharjee, Tilak; Shibata, Akinobu; Sasaki, Taisuke; Hono, Kazuhiro; Joshi, Mohit; Tsuji, Nobuhiro
Abstract: Fully recrystallized ultrafine grained (UFG) Mg-Zn-Zr-Ca alloy was successfully fabricated by a process including high pressure torsion (HPT) and subsequent rapid annealing treatment. After the HPT by one rotation, a nanocrystalline (NC) structure with an average grain size of about 100 nm and deformed characteristics was obtained. After subsequent annealing at 300 °C and 400 °C for 1 min, fully recrystallized UFG structures with average grain sizes of 0.77 μm and 0.98 μm were obtained, respectively. Room temperature tensile test revealed that the UFG Mg alloy exhibited simultaneously enhanced strength and ductility compared with those of the coarse grained counterpart. Graphical abstract: